Usefulness of the Corporate Annual Reports: Evidence from Dhaka Stock Exchange - Babu, Md. Abdullah; Hossain, Md. Muktadir (Asian Business Review, 2019)
Investors often make decisions based on information provided through different sources such as Corporate Annual Reports, Corporate news, and other media. This study is undertaken to examine the usefulness aspect of the corporate annual reports. A primary dataset composed of 38 participants of which 30 people were general investors and 8 people were stockbrokers was collected through a questionnaire survey. The study has found out that general investors perceive corporate annual reports, newspaper news, and media reviews are as the most significant sources of information. On the other hand, the study has established that stockbrokers consider company annual reports, interim reports, newspaper and media news, stock market publication, and technical analysis as the important sources of information. Also, to the general investors, most significant components of the annual reports are audit committee report, balance sheet, income statement, and statement of changes in equity, and 3 or 5-year reviews (including useful ratios). To the stockbrokers, the most essential components of the annual report are auditor's report to shareholders, balance sheet, income statement, and balance sheet notes. General investors read the balance sheet and income statement more thoroughly than any other components of annual reports.  Stockbrokers read auditor's report to shareholders, balance sheet, income statement, balance sheet notes, and income statement notes more thoroughly than any other components of annual reports.
Keywords: Corporate Annual Report; Investment Decision; General Investors; Stock Brokers